On the spatial phase distribution of cutaneous low-frequency perfusion oscillations - Borik, Stefan; Lyra, Simon; Perlitz, Volker; Keller, Micha; Leonhardt, Steffen; Blazek, Vladimir (Scientific reports, 2022)
Distributed cutaneous tissue blood volume oscillations contain information on autonomic nervous system (ANS) regulation of cardiorespiratory activity as well as dominating thermoregulation. ANS associated with low-frequency oscillations can be quantified in terms of frequencies, amplitudes, and phase shifts. The relative order between these faculties may be disturbed by conditions colloquially termed 'stress'. Photoplethysmography imaging, an optical non-invasive diagnostic technique provides information on cutaneous tissue perfusion in the temporal and spatial domains. Using the cold pressure test (CPT) in thirteen healthy volunteers as a well-studied experimental intervention, we present a method for evaluating phase shifts in low- and intermediate frequency bands in forehead cutaneous perfusion mapping. Phase shift changes were analysed in low- and intermediate frequency ranges from 0.05 Hz to 0.18 Hz. We observed that time waveforms increasingly desynchronised in various areas of the scanned area throughout measurements. An increase of IM band phase desynchronization observed throughout measurements was comparable in experimental and control group, suggesting a time effect possibly due to overshooting the optimal relaxation duration. CPT triggered an increase in the number of points phase-shifted to the reference that was specific to the low frequency range for phase-shift thresholds defined as π/4, 3π/8, and π/2 rad, respectively. Phase shifts in forehead blood oscillations may infer changes of vascular tone due to activity of various neural systems. We present an innovative method for the phase shift analysis of cutaneous tissue perfusion that appears promising to assess ANS change processes related to physical or psychological stress. More comprehensive studies are needed to further investigate the reliability and physiological significance of findings.
Keywords: Reproducibility of Results; Autonomic Nervous System; perfuze; autonomní nervový systém; Perfusion; lidé; Photoplethysmography; kůže; Skin; Humans; reprodukovatelnost výsledků; fotopletysmografie